TINJAUAN YURIDIS TERHADAP STANDARDISASI PRODUK HELM IMPOR: Juridical Review on The Standardization of Imported Helmet Products - Adhyaksa Muhammad Ilham Soekotjo; Rosdiana Saleh (Faculty of Law, Universitas Trisakti, 2024)
Business entities that carry out trade activities by importing helmets into the country without adhering to the Indonesian National Standard (SNI) is a form of violation related to Standardization and Conformity Assessment. The main issue is whether imported helmets entering the Indonesian market comply with the standardization requirements set forth in Law Nomor 20 of 2014 on Standardization and Conformity Assessment, and what sanctions are imposed on importers who violate these provisions. The study uses a normative type of research and descriptive research methods, which is then analyzed qualitatively, and conclusions are drawn using deductive reasoning. The findings indicate that business entities without an Indonesian National Standard (SNI) certificate who distribute and trade imported helmet products without being accompanied by Indonesian National Standard (SNI) standardization violate the provisions of Article 25 paragraph (4) of Law Nomor 20 of 2014. Such violations can result in criminal sanctions in accordance with Articles 65 and 67 of Law Number 20 of 2014, which include a maximum prison sentence of 5 (five) years and/or can be subject to a maximum fine of IDR 35,000,000,000.